Pembangunan Dashboard untuk Mendukung Analisis Kartu Rencana Studi dan Kartu Hasil Studi Mahasiswa - Debora Syebat Nazir; Gloria Virginia; Restyandito Restyandito; Agata Filiana; Andhika Galuh Prabawati (Jurnal Teknik Informatika dan Sistem Informasi, 2021)
At the beginning of every semester, students register for their classes resulting in KRS (student study plan) and at the end of the semester, they will receive KHS (academic transcript). KRS and KHS are recorded into the university’s system to be used for different kinds of analysis including strategic planning and accreditation. The purpose of this research is to create a dashboard to visualize data from KRS and KHS based on several Key Indicator Performance (KPI) using goal-directed design method. Performance metrics method is used to evaluate the user interface of the dashboard with 71% binary success. User Experience Questionnaire (UEQ) is also used to evaluate user experience showing scores of 1.96, 1.93, 1.77, 1.88 and 1.86 for attraction, stimulation, novelty, clarity and efficiency, respectively. These scores can be translated using the Comparison to Benchmark Scale table which shows good for both clarity and efficiency, and excellent for attraction, stimulation and novelty.